2020
DOI: 10.1002/qua.26216
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of structural, elastic, thermophysical, magneto‐electronic, and transport properties of newly tailored Mn‐based Heuslers: A density functional theory study

Abstract: Self-consistent ab-initio calculations with highly precise spin-polarized, density functional theory have been performed for the first time, to investigate the electronic structure, magnetism, transport, elasto-mechanical, and thermophysical properties of newly tailored Mn-based full-Heuslers. The cohesive and ground-state energy calculations in ferromagnetic, nonmagnetic, and antiferromagnetic states confirm the stability of materials in face-centered ferromagnetic configuration. The spin-based band structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…If Poisson's ratio ν > 0.26, the material is considered to possess a ductile character; otherwise, the material exhibits brittleness. [ 45 ] Poisson's ratios of (HfTaZrTi)C and (HfTaZrNb)C under pressure are plotted in Figure 5E.With pressure increasing from 0 to 200 GPa, Poisson's ratio ν of (HfTaZrTi)C and (HfTaZrNb)C increases from 0.23 to 0.33 and 0.20 to 0.32, respectively. It suggests that the ductility of both (HfTaZrTi)C and (HfTaZrNb)C is improved.…”
Section: Resultsmentioning
confidence: 99%
“…If Poisson's ratio ν > 0.26, the material is considered to possess a ductile character; otherwise, the material exhibits brittleness. [ 45 ] Poisson's ratios of (HfTaZrTi)C and (HfTaZrNb)C under pressure are plotted in Figure 5E.With pressure increasing from 0 to 200 GPa, Poisson's ratio ν of (HfTaZrTi)C and (HfTaZrNb)C increases from 0.23 to 0.33 and 0.20 to 0.32, respectively. It suggests that the ductility of both (HfTaZrTi)C and (HfTaZrNb)C is improved.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25–27 ] It is well known that the overall performances of TM silicides or compounds are markedly influenced by their structural feature. [ 28–32 ] Regarding thermoelectric materials, Zhang and Wang have found that the higher anisotropy of electrical conductivity results in the thermoelectric properties of the hexagonal CrSi 2 , [ 33 ] while the narrow band gap of C40 CrSi 2 is 0.3 to 0.35 eV. Oader and Venkat prepared a CrSi 2 thermoelectric thin film using the magnetron sputtering method.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric (TE) materials are in the center of worldwide research activities due to their ability to convert waste heat into electricity. [1][2][3] Direct thermal-to-electric energy conversion using TE materials may result in energy efficiency improvements in a variety of areas where waste heat is abundant. Large-scale use of TE materials is used for their conversion efficiencies, toxicity, and low availability of their constituents.…”
Section: Introductionmentioning
confidence: 99%